Rethinking Practices of Legal Pluralism in Latin America - Antonio Carlos Wolkmer (Revista Crítica de Ciências Sociais, 2023)
This paper aims to discuss Legal Pluralism from a transformative perspective as a product of community practices exercised by social collectivities that seek to address fundamental needs. In this perspective, the problem is to verify if the institutionalized pluralism in the Andean region (the constitutions of Ecuador and Bolivia) is qualified as a transforming legal pluralism, autonomous from state and with an authentic community profile. Even though this premise can be admitted, the essential question is: to what extent are its strength, validity and efficiency satisfactory inside the political-legal institutions? The result is the duality recognition of the legal pluralism that not only traditionally coexists with the State but is characterized as “subaltern” and limited by impositions of a monist culture that renews itself by keeping colonial remnants. For the discussion, a theoretical-reflective methodological approach with a critical and socio-legal content was employed, along with a specific bibliography.